Genetic variation in nutritive and anti-nutritive contents of African yam bean (sphenostylis stenocarpa) (2005)
Seeds of 20 African yam bean collections were evaluated for nutritive and antinutritive contents. Anti-nutrients were negatively correlated with protein and carbohydrate contents. Principal component analysis and the Fastclus procedure showed that collections with high anti-nutrient contents had darker seed colour.